2010
DOI: 10.1108/02610151011089519
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in entrepreneurial attitudes

Abstract: PurposeThe main objective of this article is to analyse, in depth, the role of gender differences among potential entrepreneurs, their psycho‐sociological traits and the incentives and principal obstacles women encounter when initiating a business activity.Design/methodology/approachThe approach adopted in this study focuses on university students as a fundamental source of potential future entrepreneurs. The fieldwork is based on a sample of 1,400 students at the University of Córdoba (Spain).FindingsThe resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 30 publications
4
23
0
4
Order By: Relevance
“…Concerning the gender gap debate, our results were consistent with previews scholars' findings, which concluded that business is still perceived as a male issue in the footprint (Dawson & Henley, 2015;Johansen, 2013;Minniti & Naudé, 2010). Furthermore, gaps are shown at the least in entrepreneurship education and entrepreneurial intention relation, supporting that females are less oriented towards entrepreneurship compared to males (Cañizares & García, 2010;Goktan & Gupta, 2015;Joensuu-Salo, Varamäki, & Viljamaa, 2015;Maes, Leroy, & Sels, 2014;Maresch, Harms, Kailer, & Wimmer-Wurm, 2016;Perez-Quintana, Hormiga, Martori, & Madariaga, 2017;Shirokova, Tsukanova, & Morris, 2018). Similar results were found even in other European countries (i.e.…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
“…Concerning the gender gap debate, our results were consistent with previews scholars' findings, which concluded that business is still perceived as a male issue in the footprint (Dawson & Henley, 2015;Johansen, 2013;Minniti & Naudé, 2010). Furthermore, gaps are shown at the least in entrepreneurship education and entrepreneurial intention relation, supporting that females are less oriented towards entrepreneurship compared to males (Cañizares & García, 2010;Goktan & Gupta, 2015;Joensuu-Salo, Varamäki, & Viljamaa, 2015;Maes, Leroy, & Sels, 2014;Maresch, Harms, Kailer, & Wimmer-Wurm, 2016;Perez-Quintana, Hormiga, Martori, & Madariaga, 2017;Shirokova, Tsukanova, & Morris, 2018). Similar results were found even in other European countries (i.e.…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
“…Demand‐side barriers include women’s lower predilection for launching growth‐oriented firms (Bitler, Robb, and Wolken, ), differences in risk taking (Sánchez‐Cañizares and Fuentes‐Garcia, ), lower levels of entrepreneurial self‐efficacy (Kirkwood, ), and less financial knowledge (Lusardi and Mitchell, ; Riding, Nitani and Orser, ). There remains debate about the extent to which gender influences access to loans and the terms of lending.…”
Section: Review Of Literature On Access To Finance For Women Entreprementioning
confidence: 99%
“…At the individual-level, gender differences in financial knowledge (Lusardi & Mitchell, 2011), financial self-efficacy (Amatucci & Crawley, 2011), and risk tolerance (Sánchez Cañizares & Fuentes García, 2010;Watson & Newby, 2005) have been identified as factors impeding the ability of women entrepreneurs to secure (Coleman & Robb, 2018). Limited partners included 9 lead investors and 90 novice investors, all women, who had the financial means and desire to engage in angel investing.…”
Section: Constraints Associated With Women Entrepreneurs' Access To Cmentioning
confidence: 99%